Factors Related To Attempted Suicide among Adolescence in Indonesia - Setiadi, Rizky; Saputra, Fauzan; Setiawan, Agus; Rasmun; Kalsum, Umi (International Journal of Psychosocial Rehabilitation, 2020)
Suicidal behaviour in adolescents increases with increasing demands on adolescences, such as from family members, school and society. Unfortunately, because of the number of adolescents’ prevalence of suicide is relatively small, the suicidal prevention program in adolescents is not a priority, whereas the prevalent of adolescents who attempted suicide may increase in the future. To identify factors related to suicide behaviour among adolescences in Indonesia. This was the further analysis of the 2015 Global School-based Student Health Survey (GSHS) data conducted by WHO in 75 schools in Indonesia. A sample of this study was 10,696 students selected from the data. Factors related to attempted suicide in adolescents, namely age, sex, were bullied, most of the time felt lonely, does not have any close friend, currently smoked cigarette, currently drank alcohol, currently used marijuana, had sexual intercourse, and physically inactive. The most dominant factor to attempted suicide is adolescences who does not have any close friends (AOR: 10.746; with 95% CI: 10.643 – 10.851). It is important to improve the socialization skill to prevent attempted suicide among adolescents, as well as peer group relationship, by forming a peer-supported social group in the school and society.